2017
DOI: 10.1002/mbo3.549
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reverse hybridization and ompA sequencing methods applied on Chlamydia trachomatis strains from Tunisia

Abstract: Two techniques based on ompA amplification of Chlamydia trachomatis were compared, being reverse hybridization (RHM) and ompA sequencing (OSA), to investigate the concordance between them and to study the epidemiological relevance of each method. In addition, phylogenetic analysis was performed on the ompA sequences. One hundred and seven C. trachomatis positive samples from Tunisian patients and female sex workers were analyzed using both the RHM and ompA sequencing. The overall genovar distribution obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Notably, the most prevalent genotype of isolates from patients attending an STI clinic in Tel Aviv is genotype E, which accounts for about half of the isolates. Interestingly, the genovar's distributions are similar to the report from European countries [24,27] and Tunisia [38], but present differences from Asian countries such as China, where the genotypes D and G were the most common [39], and India where genotype D was found to be most prevalent [40].…”
Section: Discussionsupporting
confidence: 70%
“…Notably, the most prevalent genotype of isolates from patients attending an STI clinic in Tel Aviv is genotype E, which accounts for about half of the isolates. Interestingly, the genovar's distributions are similar to the report from European countries [24,27] and Tunisia [38], but present differences from Asian countries such as China, where the genotypes D and G were the most common [39], and India where genotype D was found to be most prevalent [40].…”
Section: Discussionsupporting
confidence: 70%
“…In our study, C. trachomatis genotype E and F were more frequently detected in the mixed-genotype infections ( Table 2 ), which may be due to the extensive distribution of these two genotypes in China. Gallo Vaulet and Gharsallah, et al also reported that 86.7 and 76.9% of the mixed-genotype infections contained genotype E, respectively ( Gallo Vaulet et al, 2016 ; Gharsallah et al, 2018 ). Interestingly, we found that genotype G only accounted for 5.94% of the total C. trachomatis infections in our study population, but was detected in 25.0% of the mixed-genotype infections.…”
Section: Discussionmentioning
confidence: 94%
“…Sanger sequencing is a powerful tool for genotyping and has been used to determine C. trachomatis genotypes. However, it may not be suitable for identifying mixed-genotype infections of C. trachomatis since Sanger sequencing only produces one consensus sequence according to the alignment results of multiple sequencing data and the intensity of sequencing signals at each point; hence, only the dominant genotype sequence could be identified ( Gharsallah et al, 2018 ). Although the mixed-genotype infections can be identified by PCR-RFLP, hybridization methods and DNA microarray assay, these assays are not sensitive enough to identify all the mixed-genotype infections and cannot quantify genotype proportions in mixed-genotype infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation